The Effect of Service Recovery on Customer Satisfaction in J&T Express Goods Delivery Services in Palembang - Estiana Asri Fadhila; Muhammad Wadud; Roswaty Roswaty (International Journal of Marketing & Human Resource Research, 2021)
This study aims to inspect the effect of service recovery consisting of distributive, procedural, and interactional justice on customer satisfaction at J&T Express freight forwarding services in Palembang City. A total of 155 populations in this study were the users of the service company who had filed complaints. The samples of 96 were determined using the Lemeshow formula and the sample selection deployed the purposive sampling technique. Data were collected through questionnaires and analyzed using the multiple linear regression method. The findings exhibit that partially each distributive, procedural, and interactional justice has a significant effect on customer satisfaction. Likewise, simultaneously distributive, procedural, and interactional justice have a significant effect on customer satisfaction. This insight can benefit J&T Express, especially the one located in Palembang. The service company should pay attention to service recovery because this factor affects customer satisfaction.